Single-Pass SAR Interferometry with a Tandem TerraSAR-X Configuration - Ebner, Hermann; Riegger, Sebastian; Hajnsek, Irena; Hounam, David; Krieger, Gerhard; Moreira, Alberto; Werner, Marian (EUSAR-Konferenz 2004, Ulm, 25.-27.05.2004, 2004)
TanDEM-X is a mission proposal for a TerraSAR-X add-on satellite to enable high-resolution single-pass SAR interferometry. The TanDEM-X mission has the goal of generating a global Digital Elevation Model (DEM) with an accuracy corresponding to the DTED-3 specifications (12 m posting, 2 m relative height accuracy for flat terrain). This paper describes the mission concept and requirements, including several innovative aspects like operational modes, orbit selection and maintenance as well as PRF and phase synchronization. Results from a performance estimation show the achievable DEM accuracy. Finally, an overview of the potential of the TanDEM-X mission for several scientific applications is presented.
DLR Import::2019-04-03